Effect of Enclosure on Soil Carbon, Nitrogen and Phosphorus of Alpine Desert Rangeland. (4th March 2014) - Shang, Zhanhuan; Cao, Jingjuan; Guo, Ruiying; Henkin, Zalmen; Ding, Luming; Long, Ruijun; Deng, Bo
Abstract: Enclosures have been set‐up in rangelands in China since about 1980 to control grazing. This was performed in order to favour the recovery of degraded vegetation and soil. Alpine desert rangeland is an important ecosystem in China, and enclosure was considered a means of rangeland restoration for long‐term grazing. Soil properties were studied in a 6‐year enclosure experiment, which found that without grazing, vegetation cover and aboveground plant biomass increased significantly. A positive, but not significant, trend in soil bulk density was also found. However, the storage of soil carbon (C), nitrogen (N) and phosphorus (P) decreased insignificantly after 6 years of enclosure. The ratio of C:N and C:P of soil increased in the (0–10)‐cm and (10–20)‐cm layers but decreased in the (20–30)‐cm layer. In conclusion, prevention of grazing for 6 years did not significantly improve soil quality or potential carbon sequestration in the alpine desert rangelands. We recommend the removal of fences intended for rangeland and biodiversity protection from such landscapes. Copyright © 2014 John Wiley & Sons, Ltd.